Project-based learning in post-secondary education - theory, practice and rubber sling shots - Helle, Laura; Tynjälä, Päivi; Olkinuora, Erkki (Higher Education, 2006)
The purpose of the study was to explore what project-based learning is, what are the pedagogical or psychological motives supporting it, how it has been implemented and what impact it has had on learning in post-secondary education. The study is based on a qualitative review of published articles. The work revealed that the majority of articles on project-based learning are course descriptions focusing on the implementation of individual courses, whereas serious research on the topic is virtually non-existent. In addition, the term project-based learning subsumes different activities with varying purposes. Therefore, practitioners and curriculum developers are encouraged to reflect upon the purpose and possibilities of project-based learning along with students and to set realistic, clear goals. Practitioners and researchers are urged to document courses even more carefully. Several issues for further research are identified.
Keywords: coopération; développement cognitif; enseignement supérieur; pratique pédagogique